The Impact of Cellphone Bans in Schools on Student Outcomes: Evidence from Florida - David N. Figlio; Umut Özek (Munich Society for the Promotion of Economic Research - CESifo GmbH, 2025)
Cellphone bans in schools have become a popular policy in recent years in the United States, yet very little is known about their effects on student outcomes. In this study, we try to fill this gap by examining the causal effects of bans on student test scores, suspensions, and absences using detailed student-level data from Florida. Several important findings emerge. First, we show that the enforcement of cellphone bans in schools led to a significant increase in student suspensions in the short-term, especially among Black students, but disciplinary actions began to dissipate after the first year, potentially suggesting a new steady state after an initial adjustment period. Second, we find significant improvements in student test scores in the second year of the ban after that initial adjustment period. Third, the findings suggest that cellphone bans in schools significantly reduce student unexcused absences, an effect that may explain a large fraction of the test score gains. The effects of cellphone bans are more pronounced in middle and high school settings where student smartphone ownership is more common.
Keywords: I20; 330; cellphone bans in schools; student test scores; disciplinary incidents; absences; human capital